PRISM: Mounting a community‐randomised trial. Establishing partnerships with local government - Rhonda Small; Stephanie Brown; Wendy Dawson; Lyndsey Watson; Judith Lumley (Elsevier, 2004)
Abstract This paper describes initial partnership development in PRISM (Program of Resources, Information and Support for Mothers), a community‐randomised trial to improve maternal health in the first year after birth conducted in Victoria in the period 1998-2003. First, we discuss the principles underpinning community recruitment methods in PRISM that guided both our initial approaches to, and our continuing relationships with, communities. Second, we outline the strategies used to recruit communities and to establish the groundwork for ongoing partnerships over the projected six years of the study.